APPROACH TO ENGLISH AS A LINGUA FRANCA - Čalovková, Simona (Studies in Comparative Education, 2017)
During the first decade of a new millennium, interest in English as a lingua franca (ELF) increased dramatically. Therefore a lot of research has been done at a range of linguistic levels, such as lexis, grammar, pronunciation and pragmatics as well as on the morpho-syntactic properties of ELF interactions and the communi-cation strategies used by ELF speakers in order to facilitate communication and avoid misunderstandings. This has also been reflected in the approaches and attitudes towards English as a lingua franca in English Language Teaching. That is why we might need to rethink not only how English is taught, but also which kind or variety of English. We should take into account a wide range of global trends and the current transformations that English is undergoing. In this article we pay attention to the definitions and features of ELF. We also deal with the reasons why English has become a global language. We concentrate on the global nature of English, the process of globalization, and the results of various empirical research which have raised profound questions about current principle and practice in English language teaching. According to the pedagogic implications of ELF, it is necessary to take into account the key areas in particular: the nature of the language syllabus, teaching materials, approaches and methods, language assessment and the knowledge base of language teachers. Apart from this, we would like to highlight that the main aim of this article is to demonstrate the communicative advantages of an ELF approach and to raise awareness of ELF among teachers.